Boże umiłowanie Izraela (Pwt 7,7-10) - Szamocki, Grzegorz (Verbum Vitae, 2013)
According to Deut 7:7-10, love is at the root of the relationship of God Jahweh with Israel. Mutual love is inscribed in the covenant between Jahweh and his people. Jahwe’s love for Israel and its characteristics can only be explained by the nature of God. Faithful to the promises given to the fathers of Israel, God shows love to Israel. In the name of that love He chooses Israel from other nations and accompanies him in his history. Out of love He performs great works for Israel and demonstrates His power in the destruction of the enemies who hate Him. The inhabitants of the Persian province of Yehud should be considered as the first recipients of the parenesis of Deut 7:7-10. For them, the reminder of the essence of Jahweh’s love, its constancy and consequences, constituted guidance and instruction in the effort of religious-national postexilic revival and restoration. In addition, the lesson of Deut 7:7-10, according to its place in the structure of the Book of Deuteronomy, provided the basis and motivation for remaining faithful to Jahweh. It encouraged to love Him “with all your heart, with all your soul and with all your strength” (Deut 6:5).